Pengembangan Aplikasi Berbasis Android untuk Sistem Irigasi pada Sistem Pertanian Cerdas Menggunakan Flutter - Wahyu Nur Laeli Septi Ningrum; Kurniawan Dwi Irianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The agricultural sector plays a crucial role in supporting national food security. However, irrigation management that is still carried out manually often gives rise to various problems, such as water wastage, suboptimal watering, and the high time and labor demands on farmers in monitoring field conditions. Based on field observations, the watering process is still conducted manually, frequently resulting in delayed watering and uncontrolled water usage. The advancement of Internet of Things (IoT) technology provides opportunities to improve irrigation management efficiency through automated monitoring and control systems. This study aims to develop an Android-based smart irrigation system application for agriculture that can assist farmers in monitoring field conditions and controlling the irrigation system remotely. The development method employed is the Prototype model, which is a system development approach consisting of communication, quick planning, design, prototype construction, and testing phases. The application was developed using Flutter and Firebase Realtime Database and integrated with IoT devices to display soil moisture data, control irrigation pumps, display watering history, and provide real-time weather information. System testing was conducted using Black Box Testing to evaluate application functionality and the System Usability Scale (SUS) involving 10 respondents to assess the application's usability level. The Black Box Testing results demonstrated that all application functions operated with a 100% success rate, while the System Usability Scale (SUS) testing yielded an average score of 83, which falls into the Excellent category and Grade A. The findings indicate that the application was successfully developed and is capable of connecting with the IoT system in real-time, thereby facilitating more effective and efficient land monitoring and irrigation management. The contribution of this research is the development of an Android-based smart irrigation system application that integrates soil moisture monitoring, automatic and manual pump control, watering scheduling, notifications, watering history, and real-time weather information within a single platform connected to the Internet of Things (IoT).